A granulation method for guanidine acetic acid and guanidine acetic acid granules
By reacting glycine and binder with sodium hydroxide and cyanamide, controlling the cooling and insulation, guanidine acetic acid particles are prepared, which solves the problems of long granulation process, cumbersome process and insufficient particle uniformity in the prior art, and the preparation of guanidine acetic acid particles with high purity and high crystallinity is achieved.
Patent Information
- Application Number
- CN202411080515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing guanidine acetic acid granulation method has the problems of long process, cumbersome process and insufficient particle uniformity.
A method of guanidine acetic acid is adopted, which includes mixing glycine and binder to prepare it into mixed solution A, adding sodium hydroxide and heating and dissolving, and then adding cyanamide solution dropwise, controlling the cooling rate and insulating time, and obtaining guanidine acetic acid particles by centrifugation and drying.
The high purity and high crystallinity of guanidine acetate particles are achieved, with high particle uniformity, simple process and short process, reducing production costs.
Smart Images

Figure CN118993943B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of guanidinoacetic acid, and particularly relates to a granulation method of guanidinoacetic acid and guanidinoacetic acid particles. Background Art
[0002] Guanidine acetic acid is a commonly used fusing agent and intermediate, but because its nature is easily affected by air humidity, it is difficult to store under normal conditions. In order to facilitate storage and use, guanidine acetic acid often needs to be granulated.
[0003] In the prior art, when guanidine acetic acid is granulated, guanidine acetic acid powder needs to be prepared first. The preparation of guanidine acetic acid powder is generally as follows: using cyanamide, glycine and sodium hydroxide as main raw materials, first dissolving glycine and sodium hydroxide in water, adding cyanamide solution dropwise at a certain temperature to react, generating guanidine acetic acid crude product, and after the reaction is complete, refining, filtering and drying to obtain guanidine acetic acid powder, and then adding starch and hydroxypropyl methylcellulose binder to the obtained guanidine acetic acid powder, mixing and granulating through a granulating device.
[0004] The above-mentioned process for preparing guanidine acetic acid particles has technical problems such as a long process, complicated process, and insufficient particle uniformity. Summary of the invention
[0005] In view of this, the present invention provides a granulation method of guanidine acetic acid to solve the technical problems in the prior art that the traditional granulation method for preparing granules has a long and complicated process, multiple transmission equipments, and insufficient granule uniformity.
[0006] To achieve the above objectives, this application adopts the following scheme:
[0007] A granulation method for guanidine acetic acid comprises the following steps:
[0008] S10. A mixed solution A is prepared by mixing a glycine solution having a mass concentration of 20% to 40% and a binder, wherein the mass concentration of the binder in the mixed solution A is 1% to 5%;
[0009] S20. Sodium hydroxide is added to the mixed solution A, and the temperature is raised to dissolve to obtain a clear solution B;
[0010] S30. Adding the cyanamide solution dropwise to the clear solution B, and obtaining a reaction solution C after the addition is complete, wherein the molar ratio of cyanamide to glycine is (0.8 to 1):1;
[0011] S40. Cooling the reaction solution C to 40°C to 50°C and then keeping it warm for 1h to 2h, cooling it again to 10°C to 12°C and centrifuging it to obtain guanidine acetic acid particles, wherein the cooling rate is 5°C / h to 10°C / h.
[0012] Preferably, in S10, the adhesive is at least one of hydroxypropyl methylcellulose, polyethylene glycol, polyvinyl pyrrolidone, Tween, and Span.
[0013] Preferably, the adhesive is a mixture of hydroxypropyl methylcellulose and polyvinyl pyrrolidone.
[0014] Preferably, the mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:1 to 1:3.
[0015] Preferably, the mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:2.
[0016] Preferably, in S20, sodium hydroxide is added to the mixed solution A, the pH is adjusted to 9 to 10, and the mixture is heated to dissolve to obtain a clear solution B.
[0017] Preferably, in S20, the temperature is raised to 80°C to 100°C.
[0018] Preferably, in S30, the reaction temperature is 70°C to 95°C.
[0019] Preferably, in S40, the reaction solution C is cooled to 50±2°C and then kept warm for 2±0.2h, and then cooled to 10±2°C again and centrifuged to obtain guanidine acetic acid particles, wherein the cooling rate is 7±2°C / h.
[0020] A guanidine acetic acid granule is prepared by any one of the above guanidine acetic acid granulation methods.
[0021] The technical solution adopted in this application can achieve the following beneficial effects:
[0022] The present application provides a granulation method of guanidinoacetic acid, which can complete granulation in the process of preparing guanidinoacetic acid. In the initial process, the binder is mixed with the glycine solution to obtain a mixed solution A, sodium hydroxide is added dropwise to the mixed solution A to heat and dissolve, and a clear solution B is obtained. A cyanamide solution is slowly added dropwise to the clear solution B. After the reaction is completed, the cooling rate and the insulation time are controlled to achieve particle uniformity. The present application combines the binder with crystallization, forms a polymer during the crystallization process to control the change of particle size, and achieves material uniformity. The purity of the prepared guanidinoacetic acid particles is above 90%, and the crystallization rate of the prepared guanidinoacetic acid particles is above 70%. The prepared guanidinoacetic acid particles are mainly distributed between sieves of 36 meshes and 100 meshes, and the guanidinoacetic acid particles have high uniformity. Compared with the traditional guanidinoacetic acid granulation method, the present application can complete granulation in the crystallization process, and only centrifugation and drying are required to obtain the finished product. The process of preparing guanidinoacetic acid particles in the present application is short, the process is simple, and no granulation equipment is required, which has the beneficial effect of reducing costs and increasing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a magnified microscope image of the guanidinoacetic acid particles in this application. DETAILED DESCRIPTION
[0024] In order to facilitate the understanding of the present application, the present application will be described more comprehensively below in conjunction with the accompanying drawings. And the preferred implementation of the present application is given. However, the present application can be implemented in many different forms and is not limited to the implementation described herein. On the contrary, the purpose of providing these implementations is to make the disclosure of the present application more thoroughly and comprehensively understood.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] A method for granulating guanidine acetic acid, characterized in that it comprises the following steps:
[0027] S10. A mixed solution A is prepared by mixing a glycine solution having a mass concentration of 20% to 40% and a binder, wherein the mass concentration of the binder in the mixed solution A is 1% to 5%;
[0028] S20. Sodium hydroxide is added to the mixed solution A, and the temperature is raised to dissolve to obtain a clear solution B;
[0029] S30. Adding the cyanamide solution dropwise to the clear solution B, and obtaining a reaction solution C after the addition is complete, wherein the molar ratio of cyanamide to glycine is (0.8 to 1):1;
[0030] S40. Cooling the reaction solution C to 40°C to 50°C and then keeping it warm for 1h to 2h, cooling it again to 10°C to 12°C and centrifuging it to obtain guanidine acetic acid particles, wherein the cooling rate is 5°C / h to 10°C / h.
[0031] In this embodiment, a glycine solution with a mass concentration of 20% to 40% is firstly mixed with an adhesive to prepare a mixed solution A for standby use. To ensure the quality of the product, the water is deionized water, hereinafter referred to as water;
[0032] Next, the mixed solution A is placed in a dissolving kettle, and a certain amount of sodium hydroxide is added, and the temperature is raised to dissolve, thereby obtaining a clear solution B;
[0033] Then, slowly adding the cyanamide solution to the clear solution B, and obtaining a reaction solution C after the addition is complete;
[0034] The cooling rate and holding time of the reaction solution C are controlled. Specifically, the cooling rate of the reaction solution C is 5° C. / h to 10° C. / h. The reaction solution C is cooled to 40° C. to 50° C. and then kept warm for 1 h to 2 h. During this process, guanidine acetic acid crystal nuclei can be generated. The reaction solution C is then cooled to 10° C. to 12° C. at a uniform speed, centrifuged, and then dried to obtain guanidine acetic acid particles.
[0035] The method provided by the present application can complete granulation in the process of preparing guanidine acetic acid. In the initial process, the binder is mixed with the glycine solution to obtain a mixed solution A, sodium hydroxide is added dropwise to the mixed solution A to dissolve at a high temperature to obtain a clear solution B, and a cyanamide solution is slowly added dropwise to the clear solution B. After the reaction is completed, the cooling rate and the holding time are controlled to achieve particle uniformity. The present application combines the binder with crystallization, and forms a polymer to control the change of particle size during the crystallization process to achieve material uniformity. The purity of the prepared guanidine acetic acid particles is above 90%, and the crystallization rate of the prepared guanidine acetic acid particles is above 70%. The prepared guanidine acetic acid particles are mainly distributed between sieves of 36 mesh and 100 mesh, and the guanidine acetic acid particles have high uniformity. Compared with the traditional guanidine acetic acid granulation method, the present application can complete granulation during the crystallization process, and only centrifugation and drying are required to obtain the finished product. The process of preparing guanidine acetic acid particles is short and simple, and does not require the aid of granulation equipment, which has the beneficial effect of reducing costs and increasing efficiency.
[0036] The binder is at least one of hydroxypropyl methylcellulose, polyethylene glycol, polyvinyl pyrrolidone, Tween and Span. The binder is added and dissolved together with glycine in the initial process. To ensure the quality of the product, the binders are all of pharmaceutical grade. The purity of the guanidine acetic acid particles prepared by the five binders is higher than 90%. When the binder is polyvinyl pyrrolidone, the crystallization rate of the prepared guanidine acetic acid particles is higher, which is 84.2%. When the binder is hydroxypropyl methylcellulose, the crystallization rate of the guanidine acetic acid particles prepared is second, which is 82.6%.
[0037] Preferably, the binder is a mixture of hydroxypropyl methylcellulose and polyvinyl pyrrolidone, wherein the mass ratio of the hydroxypropyl methylcellulose to the polyvinyl pyrrolidone is 1:1 to 1:3. When the mass ratio of the hydroxypropyl methylcellulose to the polyvinyl pyrrolidone is 1:1 to 1:3, the crystallization rate of the prepared guanidine acetic acid particles is higher than that of the guanidine acetic acid particles prepared when the hydroxypropyl methylcellulose and the polyvinyl pyrrolidone are used as binders alone.
[0038] Furthermore, the mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:2. When the mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:2, the crystallization rate of the prepared guanidine acetic acid particles is better, which is 95.8%.
[0039] Specifically, in S20, sodium hydroxide is added to the mixed solution A, the pH is adjusted to 9 to 10, and the mixture is heated to dissolve to obtain a clear solution B.
[0040] Specifically, in S20, the temperature is raised to 80°C to 100°C.
[0041] Specifically, in S30, the reaction temperature is 70°C to 95°C.
[0042] Preferably, in S40, the reaction solution C is cooled to 50±2°C and then kept warm for 2±0.2h, and then cooled to 10±2°C again for centrifugation to obtain guanidine acetic acid particles, wherein the cooling rate is 7±2°C / h. Under this condition, the prepared guanidine acetic acid particles have a 16-mesh sieve pass rate of 100%, a 36-mesh sieve pass rate of 94%, a 100-mesh sieve pass rate of 7%, and a 120-mesh sieve pass rate of 2%. The guanidine acetic acid particles are mainly distributed between 36 and 100 mesh sieves, and the uniformity of the prepared guanidine acetic acid particles is better.
[0043] A guanidinoacetic acid granule is prepared by any one of the above-mentioned guanidinoacetic acid granulation methods. The purity of the guanidinoacetic acid granules prepared by the above-mentioned method is above 90%, the crystallinity is greater than 70%, the guanidinoacetic acid granules are mainly distributed between 36 mesh and 100 mesh sieves, and the uniformity of the prepared guanidinoacetic acid granules is better.
[0044] The following specific experimental examples are used to further illustrate the technical solutions and technical effects of the present invention. It should be noted that the following experimental examples are only for further explaining the present invention and do not limit the technical solutions of the present invention.
[0045] 1. Experimental Materials and Methods
[0046] 1.1 Experimental Materials
[0047] Glycine, water, sodium hydroxide, cyanamide, and binders (hydroxypropyl methylcellulose, polyethylene glycol, polyvinyl pyrrolidone, Tween, and Span) are all commercially available.
[0048] 1.2 Experimental methods
[0049] The experiment was divided into five treatment groups, namely, Example 1, Example 2, Example 3, Example 4, and Example 5. Different guanidine acetic acid particles were prepared by the five treatment groups. The mass of the prepared guanidine acetic acid particles was weighed, the crystallization rate of the prepared guanidine acetic acid particles was calculated according to the formula, the purity was detected, and the particle size distribution was detected using sieves of different mesh sizes.
[0050] The crystallization rate of guanidine acetic acid particles was calculated by the following formula:
[0051] Crystallization rate of guanidinoacetic acid particles = (actual crystallization amount of guanidinoacetic acid particles × purity) / (theoretical crystallization amount of guanidinoacetic acid particles × yield);
[0052] Among them, the guanidinoacetic acid particles are crystals of guanidinoacetic acid; in the present application, glycine and cyanamide mainly react to generate guanidinoacetic acid, and the binder accounts for only 5% of the total solution. According to actual detection by technicians in this field, the yield of guanidinoacetic acid is about 90%. For the convenience of calculation, the guanidinoacetic acid yield in the crystallization rate of guanidinoacetic acid particles in the following embodiments is calculated as 90%.
[0053] 2. Example 1: Effect of adding different types of adhesives on experimental results
[0054] In this embodiment, five experimental groups are set up, and 266.7g of glycine solution (the mass concentration of the glycine solution is 30%) and 8.2g of adhesive are added to each experimental group, wherein the adhesive of the first group is hydroxypropyl methylcellulose, the adhesive of the second group is polyethylene glycol, the adhesive of the third group is polyvinyl pyrrolidone, the adhesive of the fourth group is Tween, and the adhesive of the fifth group is Span, and five mixed solutions A are prepared; sodium hydroxide is added dropwise to the five mixed solutions A, the pH of the mixed solution A is adjusted to 9, and the temperature is raised to 90°C to dissolve, and five clear solutions B are obtained; 84g of cyanamide solution (the mass concentration of the cyanamide solution is 50%) is slowly added dropwise to the five clear solutions B, the reaction temperature is 80°C, and five reaction solutions C are obtained after the reaction is completed; the reaction solution C is cooled at a cooling rate of 7°C / h, cooled to 50°C and kept warm for 2h, then cooled to 10°C at a uniform speed and centrifuged, and five guanidine acetic acid particles are obtained respectively, and the adhesive is specifically shown in Table 1:
[0055] Table 1 Example 1 Different types of adhesives
[0056]
[0057] In Example 1, five kinds of guanidinoacetic acid particles were prepared respectively, and their purity and mass were tested respectively. The crystallization rate of the guanidinoacetic acid particles was calculated according to the formula, and the particle size distribution was detected. The results are shown in Table 2:
[0058] Table 2 Test results of guanidine acetic acid particles in Example 1
[0059]
[0060]
[0061] It can be seen from the above experiments that guanidinoacetic acid particles can be prepared by the granulation method of guanidinoacetic acid provided in the present application, and the data in Table 2 above show that the purity of the guanidinoacetic acid particles prepared in the five groups of experiments in Example 1 is all above 90%, which meets the purity standard of guanidinoacetic acid particles; the uniformity of the prepared guanidinoacetic acid particles is relatively high. Although the 16-mesh sieve pass rate is 100%, the 36-mesh sieve pass rate is 94%, the 100-mesh sieve pass rate is 7%, and the 120-mesh sieve pass rate is 2%. Therefore, the prepared guanidinoacetic acid particles are mainly distributed between the 36-mesh and 100-mesh sieves, so the uniformity of the guanidinoacetic acid particles is relatively high. Please refer to Figure 1 , Figure 1 The guanidine acetic acid particles prepared by the third group of experimental examples; it can also be seen from the data in Table 2 that when the binder is polyvinyl pyrrolidone, the crystallization rate of the prepared guanidine acetic acid particles is higher, which is 84.2%. When the binder is hydroxypropyl methylcellulose, the crystallization rate of the prepared guanidine acetic acid particles is second, which is 82.6%.
[0062] 3. Example 2: Effect of Adhesive Concentration on Experimental Results
[0063] The difference between this embodiment 2 and the third group of experiments in the above embodiment 1 is that the concentration of the binder (polyvinyl pyrrolidone) in the mixed solution A is changed. The concentration of the polyvinyl pyrrolidone is specifically shown in Table 3:
[0064] Table 3 Concentration of polyvinyl pyrrolidone in Example 2
[0065]
[0066] In Example 2, two kinds of guanidinoacetic acid particles were prepared, respectively, and their purity and mass were tested, respectively. The crystallization rate of the guanidinoacetic acid particles was calculated according to the formula, and the particle size distribution was detected. The results are shown in Table 4:
[0067] Table 4 Test results of guanidine acetic acid particles in Example 2
[0068]
[0069]
[0070] It can be seen from Table 4 that the concentration of the binder (polyvinyl pyrrolidone) affects the crystallization rate of the guanidinoacetic acid particles. In the sixth group of experiments, when the concentration of the polyvinyl pyrrolidone was 1%, the crystallization rate of the prepared guanidinoacetic acid particles was 81.1%; in the seventh group of experiments, when the concentration of the polyvinyl pyrrolidone was 5%, the crystallization rate of the prepared guanidinoacetic acid particles was 79.7%; both were lower than the crystallization rate of 84.2% of the guanidinoacetic acid particles prepared when the concentration of the polyvinyl pyrrolidone was 3% in the third group of experiments in Example 1 above.
[0071] 4. Example 3: Effect of the combination of adhesives on experimental results
[0072] The difference between this embodiment 3 and the first group of experiments in the above embodiment 1 is that the adhesive is hydroxypropyl methyl fiber and polyvinyl pyrrolidone, and the mass ratio of the hydroxypropyl methyl fiber and polyvinyl pyrrolidone is shown in Table 5:
[0073] Table 5 Mass ratio of hydroxypropyl methylcellulose and polyvinyl pyrrolidone in Example 3
[0074] Experimental groups Hydroxypropyl methylcellulose(g) Polyvinylpyrrolidone (g) Proportion Group 8 4.1 4.1 1:1 Group 9 2.7 5.5 1:2 Group 10 2.05 6.15 1:3
[0075] In Example 3, three kinds of guanidinoacetic acid particles were prepared respectively, and their purity and mass were tested respectively. The crystallization rate of the guanidinoacetic acid particles was calculated according to the formula, and the particle size distribution was detected. The results are shown in Table 6:
[0076] Table 6 Test results of guanidine acetic acid particles in Example 3
[0077]
[0078] It can be seen from the data in Table 6 that when the hydroxypropyl methyl fiber and the polyvinyl pyrrolidone are mixed in a mass ratio of 1:1 to 1:3 as a binder, the crystallization rate of the guanidine acetic acid particles can be further improved. In particular, when the mass ratio of the hydroxypropyl methyl fiber and the polyvinyl pyrrolidone is 1:2, the effect is better, and the crystallization rate of the prepared guanidine acetic acid particles can reach 95.8%.
[0079] 5. Example 4: Effect of cooling rate on experimental results
[0080] The difference between this embodiment 3 and the third group of experiments in the above embodiment 1 is that the cooling rate is changed. The cooling rate is specifically shown in Table 7:
[0081] Table 7 Concentration of polyvinyl pyrrolidone in Example 4
[0082]
[0083] In Example 4, two kinds of guanidinoacetic acid particles were prepared, respectively, and their purity and mass were tested, respectively. The crystallization rate of the guanidinoacetic acid particles was calculated according to the formula, and the particle size distribution was detected. The results are shown in Table 8:
[0084] Table 8 Test results of guanidine acetic acid particles in Example 4
[0085]
[0086] It can be seen from the data in Table 8 that the cooling rate affects the particle size distribution of the prepared guanidine acetic acid particles. When the cooling rate is 5°C / h, although the 16-mesh sieve pass rate is 100%, the 36-mesh sieve pass rate is 98%, the 100-mesh sieve pass rate is 24%, and the 120-mesh sieve pass rate is 8%. Therefore, the prepared guanidine acetic acid particles are mainly distributed between the 36-mesh and 120-mesh sieves; when the cooling rate is 10°C / h, the prepared guanidine acetic acid particles are also basically distributed between the 36-mesh and 120-mesh sieves. Compared with the third group of experiments in the above Example 1 (the guanidine acetic acid particles are basically distributed between the 36-mesh and 100-mesh sieves), the uniformity of the guanidine acetic acid particles prepared in this example is not as good as the uniformity of the guanidine acetic acid particles prepared in the third group of experiments in Example 1.
[0087] 6. Example 5: Effect of holding time on experimental results
[0088] The difference between this embodiment 5 and the third group of experiments in the above embodiment 1 is that the heat preservation time is changed. The heat preservation time is specifically shown in Table 9:
[0089] Table 9 Concentration of polyvinyl pyrrolidone in Example 5
[0090]
[0091] In Example 5, two kinds of guanidinoacetic acid particles were prepared, respectively, and their purity and mass were tested, respectively. The crystallization rate of the guanidinoacetic acid particles was calculated according to the formula, and the particle size distribution was detected. The results are shown in Table 10:
[0092] Table 10 Test results of guanidine acetic acid particles in Example 5
[0093]
[0094] It can be seen from the data in Table 10 that the holding time also affects the particle size distribution of the prepared guanidine acetic acid particles. When the holding time is 1 h, although the 16-mesh sieve pass rate is 100%, the 36-mesh sieve pass rate is 98%, the 100-mesh sieve pass rate is 25%, and the 120-mesh sieve pass rate is 7%. Therefore, the prepared guanidine acetic acid particles are mainly distributed between the 36-mesh and 120-mesh sieves; when the holding time is 1.5 h, the prepared guanidine acetic acid particles are also basically distributed between the 36-mesh and 120-mesh sieves. Compared with the third group of experiments in the above Example 1 (the guanidine acetic acid particles are basically distributed between the 36-mesh and 100-mesh sieves), the uniformity of the guanidine acetic acid particles prepared in this example is not as good as the uniformity of the guanidine acetic acid particles prepared in the third group of experiments in Example 1.
[0095] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for granulating guanidine acetic acid, characterized in that: The steps include: S10. A mixed solution A is prepared by mixing a glycine solution having a mass concentration of 20% to 40% and a binder, wherein the mass concentration of the binder in the mixed solution A is 1% to 5%, and the binder is at least one of hydroxypropyl methylcellulose, polyethylene glycol, polyvinyl pyrrolidone, Tween, and Span; S20. Sodium hydroxide was added to the mixed solution A, and the temperature was raised to dissolve to obtain a clear solution B; S30. Adding a cyanamide solution dropwise to the clear solution B, and obtaining a reaction solution C after completion of the addition, wherein the molar ratio of cyanamide to glycine is (0.8 to 1): 1; S40. The reaction solution C is cooled to 40°C to 50°C and then kept warm for 1 to 2 hours. After being kept warm, the solution is cooled again to 10°C to 12°C and centrifuged to obtain guanidine acetic acid particles, wherein the cooling rate is 5°C / h to 10°C / h.
2. The method for preparing guanidine acetic acid according to claim 1, wherein The adhesive is a mixture of hydroxypropyl methylcellulose and polyvinyl pyrrolidone.
3. The granulation method of guanidine acetic acid according to claim 2, characterized in that The mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:1 to 1:
3.
4. The method for preparing guanidine acetic acid according to claim 3, characterized in that: The mass ratio of the hydroxypropyl methyl fiber to the polyvinyl pyrrolidone is 1:
2.
5. The method for preparing guanidine acetic acid according to claim 1, characterized in that: In S20, sodium hydroxide is added to the mixed solution A to adjust the pH to 9 to 10, and the mixture is heated to dissolve to obtain a clear solution B.
6. The method for granulating guanidine acetic acid according to claim 1 or 5, characterized in that: In the S20, the temperature is raised to 80°C to 100°C.
7. The method for preparing guanidine acetic acid according to claim 1, characterized in that: In the S30, the reaction temperature is 70°C to 95°C.
8. The method for preparing guanidine acetic acid according to claim 1, wherein: In the S40, the reaction solution C is cooled to 50±2°C and then kept warm for 2±0.2 h. After being kept warm, the reaction solution C is cooled to 10±2°C again and centrifuged to obtain guanidine acetic acid particles, wherein the cooling rate is 7±2°C / h.
Citation Information
Patent Citations
Abrasion-resistant free-flowing glycocyamine-containing mouldings and methods for their production
CN101778574A